Predictors of anastomotic strictures following œsophageal atresia repair. Issue 5 (25th February 2022) - Aumar, Madeleine; Sfeir, Rony; Pierache, Adeline; Turck, Dominique; Gottrand, Frederic
Abstract : Objectives: To identify the risk factors for anastomotic, refractory and recurrent strictures and to establish whether anastomotic stricture is associated with antireflux surgery. Design: This prospective national multicentre study included all infants born with oesophageal atresia (OA) over an 8-year period. Data on OA and complications were collected at birth and at 1 year old. Univariate and multivariate analyses were conducted. Results: 1082 patients from 37 centres were included in the study. The prevalence of anastomotic stricture at 1 year old was 23.2%. Anastomosis under tension (defined by the surgeon at the time of repair) and delayed anastomosis (defined as anastomosis performed more than 15 days after birth, excluding delays due to prematurity or severe cardiac diseases) were found to be independent risk factors for anastomotic stricture (2.3 (1.42–3.74) and 4.02 (2.12–7.63), respectively). Patients with anastomotic stricture had a 2.3-fold higher rate of fundoplication compared with others (p=0.001). Anastomosis under tension and delayed anastomosis were found to be independent risk factors for recurrent stricture (1.92 (1.10–3.34) and 5.73 (2.71–12.14), respectively), while delayed anastomosis was the only risk factor for refractory stricture (8.30 (3.34–20.64)). There was a 2.39-fold (1.42–4.04) higher rate of fundoplication in the anastomotic stricture group than in the group without anastomotic stricture (p=0.001). Conclusions: Patient-related anatomical factors leading to anastomosis under tension and delayed anastomosis increase the risk of anastomotic stricture. Abstract : Large study of all babies born with oesophageal atresia in France over an 8 year period with follow up to 1 year. Anastomotic stricture identified in 23% of cases with independent risk factors identified including one (delayed anastomosis) previously unreported.